Daily melatonin protects the endothelial lineage and functional integrity against the aging process, oxidative stress, and toxic environment and restores blood flow in critical limb ischemia area in mice - Lee, Fan‐Yen; Sun, Cheuk‐Kwan; Sung, Pei‐Hsun; Chen, Kuan‐Hung; Chua, Sarah; Sheu, Jiunn‐Jye; Chung, Sheng‐Ying; Chai, Han‐Tan; Chen, Yi‐Ling; Huang, Tien‐Hung; Huang, Chi‐Ruei; Li, Yi‐Chen; et al. (Journal of pineal research, 2018)
We tested the hypothesis that daily melatonin treatment protects endothelial lineage and functional integrity against the aging process, oxidative stress/endothelial denudation (ED), and toxic environment and restored blood flow in murine critical limb ischemia (CLI). In vitro study using HUVECs, in vivo models (ie, CLI through left femoral artery ligation and ED through carotid artery wire injury), and model of lipopolysaccharide‐induced aortic injury in young (3 months old) and aged (8 months old) mice were used to elucidate effects of melatonin treatment on vascular endothelial integrity. In vitro study showed that menadione‐induced oxidative stress (NOX‐1/NOX‐2), inflammation (TNF‐α/NF‐kB), apoptosis (cleaved caspase‐3/PARP), and mitochondrial damage (cytosolic cytochrome c) in HUVECs were suppressed by melatonin but reversed by SIRT3‐siRNA (all P < .001). In vivo, reduced numbers of circulating endothelial progenitor cells (EPCs) (C‐kit/CD31+/Sca‐1/KDR+/CXCR4/CD34+), and angiogenesis (Matrigel assay of bone marrow‐derived EPC and ex vivo aortic ring cultures) in older (compared with younger) mice were significantly reversed through daily melatonin administration (20 mg/kg/d, ip) (all P < .001). Aortic vasorelaxation and nitric oxide release were impaired in older mice and reversed in age‐match mice receiving melatonin (all P < .01). ED‐induced intimal/medial hyperplasia, reduced blood flow to ischemic limb, and angiogenesis (reduced CD31+/vWF+ cells/small vessel number) were improved after daily melatonin treatment (all P < .0001). Lipopolysaccharide‐induced aortic endothelial cell detachment, which was more severe in aged mice, was also alleviated after daily melatonin treatment (P < .0001). Daily melatonin treatment protected both structural and functional integrity of vascular endothelium against aging‐, oxidative stress‐, lipopolysaccharide‐, and ischemia‐induced damage probably through upregulating the SIRT signaling pathway.